2007
DOI: 10.1094/cchem-84-1-0088
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Head Rice Yield for Surface Lipid Content (Degree of Milling) Variation

Abstract: Cereal Chem. 84(1):88-91Head rice yield (HRY) is the primary parameter used to quantify rice milling quality. However, HRY is affected by the degree of milling (DOM) and thus HRY may not be comparable between different lots if the DOM is different. The objective of this study was to develop a method by which HRY values can be adjusted for varying DOM values when measured by surface lipid content (SLC). Seventeen rough rice lots including long-grain and medium-grain cultivars and hybrids were harvested from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…The obtained brown rice, following the method modified from Andrews et al (1992), was subsequently milled with the rice miller friction type milling machine (Sinthavee, Khok Samrong, Lop Buri, TH) under 200 combinations of three conditional factors (e.g., Chen et al 1997;Perdon et al 2001;Cooper and Siebenmorgen 2007) (Fig. 1).…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained brown rice, following the method modified from Andrews et al (1992), was subsequently milled with the rice miller friction type milling machine (Sinthavee, Khok Samrong, Lop Buri, TH) under 200 combinations of three conditional factors (e.g., Chen et al 1997;Perdon et al 2001;Cooper and Siebenmorgen 2007) (Fig. 1).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Surface lipid content (SLC) from 5 g of head rice of each sample was extracted in Soxtec-Avanti 2050 (Foss Co., Denmark) according to the method of Cooper and Siebenmorgen (2007) who adapted from Mastsler and Siebenmorgen (2005). Prior to extraction, the sample in the cellulose extraction thimble was oven-dried for 1 h at 100°C to reduce moisture content.…”
Section: Surface Lipid Content Analysismentioning
confidence: 99%
“…Milling rice to lesser degrees, that is, leaving more bran on milled kernels, can lead to greater milling yields and human nutritional benefits, as well as potential energy savings (Cooper and Siebenmorgen, 2007;Lanning and Siebenmorgen, 2011;Roy et al, 2008). From an energy-use standpoint, milling rice to lesser degrees requires shorter milling durations (Cooper and Siebenmorgen, 2007), thus consuming less energy during milling operations.…”
Section: Introductionmentioning
confidence: 99%
“…Cracking and fissures can appear before and during harvest, during storage and during the drying process, which results in kernel breakage [6,7]. Furthermore, the degree of milling, handling procedures, harvest moisture and moisture content, immature kernels, diseases, chalkiness and mixture of slender type influences the HRY [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al [24] showed that multiple rice quality parameters, such as size, HRY and chalkiness, could be determined by using image analysis on the milled rice. However, since the degree of milling affects the HRY [8], it would be preferable to measure the paddy rice directly. Thus, an instrument that combines texture measurements, colour, size and shape as well as translucency of the kernels with limited manual handling and preparations of the samples would have a great potential for measuring the quality of rice kernels.…”
Section: Introductionmentioning
confidence: 99%